The Correlation between Reading Speed and Reading Comprehension of the Second Semester Students of IIK Pelamonia Makassar - Fibri Indira Lisanty AD; Hermini Hermini (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
This research aims at finding out the correlation between reading speed and reading comprehension of the second semester students of IIK Pelamonia Makassar. This research deals with the correlation between reading speed and reading comprehension. There are two steps of activity, reading speed means use time efficiently and reading comprehension means understand the passage. The population of this research was the second semester of Pharmacy major at IIK Pelamonia Makassar which consisted of four classes. The researcher took only one class as the sample, Class A which is consisted of 30 students. The investigation shows that the coefficient correlation of the two variable (rxy) is worse than the critical value or (r), r < critical value of (r) with (N) = 30 on 99 % level of significance is 0.361. It mean that there is no significant correlation between reading speed and reading comprehension of the second of Pharmacy major at IIK Pelamonia Makassar .